Prevalence of Non Communicable Diseases and Its Risk Factors among the Non-Teaching Staff of Medical College using WHO STEPS - Priya Rathi; Pracheth Raghuveer; Varun Narendra; Madhavi Bhargava (Medsci Publications, 2018)
Introduction: Non-communicable diseases (NCDs) contribute to 65% of all the deaths and 80% of these are in developing countries. Medical colleges have a large workforce with risk for NCDs similar to general population. Methodology: A cross-sectional survey among the 65 of 88 non-teaching staff members of the medical college was done to screen for NCDs using WHO STEPS with necessary modifications. This was done as part of student research project through regular undergraduate curriculum where the undergraduate medical students are taught basic research skills. Results: There were six self-reported diabetics and five self-reported hypertensives. Risk factors such as high salt intake (77%), high waist-hip ratio (15% women), and overweight (22%) were detected. Conclusion: The exercise gave an opportunity for screening and spreading awareness for health promotion and risk reduction for NCDs.